Traffic characteristics of car parks in NTU campus - Chang, Zhi Ling. (2010)
The report, “Traffic characteristics of car parks in NTU campus” studies the parking characteristics of the different car parks in the NTU campus study. The utilization rate and illegal parking situation of each car park would be studied and compared to find out which are the more heavily utilized car parks. As this study is going to relate the parking needs of the students and staff of NTU, only the car parks located in the North and South Spines were selected. There were a total of 14 car parks selected for the study, and the author would be in charge of analyzing Car Parks A, C, D, E and F. Each of these car parks contain an Electronic Parking System (EPS) which records the individual In-Vehicle Units (IU) Number of each vehicle, and their respective entry and exit timings into the car park. Data from the EPS of the car parks would be collected from the Office of Planning Management (OFPM), and using these data, the parking accumulation graph and parking duration distribution histograms would be plotted using Microsoft Excel. The average occupancy rate, peak occupancy rate, average parking duration and situation of illegal parking would subsequently be analysed. Frequent site visits to the car parks would be conducted to verify the results obtained. For car parks located at the North Spine, results obtained showed that strategically located free car parks such as Car Parks C, D, and E were very highly utilized with Car Park D having the highest occupancy rate and most illegal parking observed. On the other hand, Car Park F (free of charge) was not highly utilized due to its poor location. Car Park A which has charges imposed on their users had a very low occupancy rate, with no illegal parking observed at all. For the South Spine, majority of the car parks were relatively underutilized. This could be due to the smaller cohort of students and staff in the academic buildings of the South Spine. In order to alleviate the highly utilized car parks, several recommendations were made. The school could charge the free car parks, and increase the frequency of free shuttle buses within the campus to discourage students from driving to school.